Modeling of asphaltene precipitation - part I: comparative study for asphaltene precipitation envelope prediction methods - Ali, Ali A.; Hameed Abdul-Majeed, Ghassan; Mohmmed, Abdalellah O. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
The solubility of asphaltenes in crude oils is predominantly influenced by variations in temperature, pressure, and oil composition. These alterations can precipitate asphaltene deposition, resulting in diminished permeability, obstruction of wells and auxiliary surface facilities, and ultimately, a reduction or cessation of production. Therefore, it is imperative for upstream and downstream processing engineers to comprehend and predict asphaltene phase behavior to implement effective preventative and remedial strategies and minimize costs. Asphaltene precipitation can be predicted through the application of solubility and colloidal theories. In this study, cubic equations of state and cubic-plus-association equations of state are utilized as solubility theory-based methodologies. The advanced versions of the Peng-Robinson (APR78) and Soave-Redlich-Kwong (ASRK) cubic equations of state are compared with cubic-plus-association (CPA) equations of state using Multiflash software to predict fluid and asphaltene phase behavior. The simulation results demonstrate a strong correlation between the ASRK model and the CPA model, with a minor deviation from the results of the APR78 model. This observation suggests that these models can effectively predict asphaltene behavior and yield acceptable results when compared to experimental data for fluid and asphaltene. Considering the likelihood of asphaltene deposition within wells, hence, it is recommended to develop a model to determine the locations and quantities of deposition.